Risk Assessment of Hepatitis B Patients of Northern Areas of Pakistan: A case control study - Alamzeb Jadoon, Muhammad Adil Khan, Muhammad Safdar, Zahid Irfan Marwat, Ayesha Gohier, Muhammad Umer Farooq, Safdar Irfan Marwat (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hepatitis B (HBV) is a common chronic viral disease that affects liver. About 7% people worldwide are infected with HBV with the majority of the cases seen in developing countries with limited medical facilities. It is a blood-borne disease and contributing factors for risk assessment varies from place to place. Aim: To acquire key factors for risk assessment of hepatitis B patients of the northern area of Pakistan. Methods: A case-control study was done among the patients visiting Ayub Teaching Hospital for a regular checkup. The sample included 80 cases and 80 controls by the non-probability convenient method. Data was collected using a structured questionnaire and analyzed by SPSS 23. Frequencies, mean, standard deviation, p values and odds ratio were calculated. Results: A total of 160 subjects were included in this study(80 controls & 80 cases of HBV. Mean age for cases was 38.74±13.597 years. Odds ratios and p values were calculated for different factors. The odds ratio for a history of blood transfusion, sharing toothbrushes, eliciting injectable drugs, history of recent dental procedure and surgical procedure were 1.581, 1.116, 2.206, 1.581 and 1.165 respectively. Conclusion: Although not significant, yet, low socioeconomic status, family history and piercing ears/nose and tattoos resulted in a higher percentage ascontributing factors of HBV infection. In Northern areas of Pakistan, these factors for risk assessment of hepatitis B should be kept in mind and proper disease awareness and primary prevention program should be observed.